Yield, Yield Components, Soil Chemical Properties, Plant Physiology, and Phosphorus Use Efficiency in Soybean Genotypes - Moreira, A.; Moraes, L. A. C.; Moretti, L. G. [UNESP] (Taylor & Francis Inc, 2017)
Expansion of soybean [Glycine max (L.) Merrill] cultivated in Brazil to regions with low fertility soils gave rise to studies on the possibility of obtaining highly productive cultivars with high nutrient use efficiency. An experiment in greenhouse conditions was conducted to assess phosphorus (P) use efficiency (PUE) by 13 soybean genotypes. The genotypes were grown in an Ustoxix Quartzipsamment with two P rates [0 (no P application) and 150 mg P kg(-1)], whose source was monoammonium phosphate (MAP, P2O5 44%). Shoot dry weight (SDW), grain yield (GY), grain harvest index (GHI), relative yield (RY), and physiological components (photosynthetic rate, stomatal conductance, respiratory rate, and internal CO2 concentration) were influenced by soybean genotypes and P rates. Genotypes BMX Apolo RR, BRS 360RR, BRS 378RR, CD 219RR, DM 2302RR, TMG 7161RR, and Vtop RR were classified as non-efficient and non-responsive to P application, while BMX Potencia RR, Vmax RR, FPS Solar RR, NA 5909RR, TMG 1066RR, and M 6210 IPRO were classified as efficient and responsive. Phosphorus application increased the values of physiological components, which was not observed for N, K, Ca, Mg, and S concentration in the leaves and grains. Soybean genotypes selection for increased P efficiency could help growers overcome the problem of soybean cultivation on new areas or degraded pastures.
Keywords: Glycine max; nutritional status; soil fertility; yield components